2017
DOI: 10.5812/iji.15842
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Conditions for Bacteriocin Production by Soil Isolates Pediococcus pentosaceus LB44 and Weissella confusa LM85

Abstract: Background: Bacteriocins are antimicrobial proteins or peptides secreted in the culture medium during the growth of bacteria. Bacteriocin production is influenced by various physical parameters such as pH, temperature, NaCl concentration, and carbon source. Objectives: The current study aimed at optimizing the culture conditions for higher growth and production of bacteriocins by the soil isolates, Pediococcus pentosaceus LB44, and Weissella confusa LM85. Methods: Growth of LB44 and LM85 isolates was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…sakei 2a, bacteriocin production was stunted in the presence of 4% of NaCl (Barbosa et al, 2018). with the increase of NaCl (Kaur & Kumar Tiwari, 2017). The results also indicated that there was a synergistic effect of combining phosphate, carbon, and nitrogen sources.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…sakei 2a, bacteriocin production was stunted in the presence of 4% of NaCl (Barbosa et al, 2018). with the increase of NaCl (Kaur & Kumar Tiwari, 2017). The results also indicated that there was a synergistic effect of combining phosphate, carbon, and nitrogen sources.…”
Section: Discussionmentioning
confidence: 79%
“…Three strains ( L. pentosus NRC AM5, L. plantarum NRC AM7 and L. pentosus NRC AM8) could survive in 10% of NaCl. In a separate study utilizing a similar range of NaCl concentration in MRS medium, P. pentosaceus LB44 and Weissella confusa LM85 were shown to exhibit the highest optical density (OD 600 ) only in the control MRS medium, whereby growth gradually decreased with the increase of NaCl (Kaur & Kumar Tiwari, 2017). The results also indicated that there was a synergistic effect of combining phosphate, carbon, and nitrogen sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, P. pentosaceus LB44 grew up to OD600 1.2 to 1.5 at pH 5.0 to 8.0. However, they grew to very less extent (OD600 0.1 to 0.3) under highly acidic (pH 3.0 and 4.0) and alkaline (pH 9.0 and 10.0) conditions (Kaur & Kumar, 2017). Meanwhile, in the 0.5% eggshell group, the maximum abundance of bacteria was reached at 0.5–2 days, and then the bacterial abundance gradually decreased after the pH dropped to below 3.8.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocinogenic strains classi ed as P. pentosaceus with anti-Listeria activity were identi ed from Brazilian artisanal cheese [20], intestine of Mimachlamys nobilis [23], ermented Appam batter [24]. According to Ramanjeet Kaur et al [25], Pediococcus pentosaceus LB44 could grow and produce bacteriocin under acidic and alkaline conditions. The strain L5 in current study which was designated as P. pentosaceus Z-1 isolated from Jinhua ham expand the bacteriocin production scope from food resources of fermented meat product.…”
Section: Identi Cation Of Pediococcus Pentosaceusmentioning
confidence: 99%